Cuidados de enfermería en pacientes hipertensos de 45 a 75 años, que acuden al Dispensario 22 de febrero del cantón Balzar, provincia del Guayas, primer semestre del año 2013 - Charcopa Bravo, Bethy Esperanza (2013)
The Ministry of Public Health of Ecuador , in their notifications Epidemiology reported that the most common problems in people over 60 were hypertension , obesity , diabetes mellitus type 2 ( DM2) , hypercholesterolemia, and some kidney diseases, limited information on profile of health and nutrition at national level in this population and accelerated demographic transition put on show the need for updated data Hypertension was defined as the level of systolic blood pressure ( SBP ) greater than or equal to 140 mm Hg, or the level of diastolic blood pressure (DBP ) greater than or equal to 90 mm Hg. When systolic blood pressure (SBP ) is equal to or greater than 160 mmHg , One purpose of nursing is to project health preventive measures and the promotion of health services to the community , is this reason it is necessary to conduct the study called nursing in hypertensive patients aged 45 to 75 years old, attending the clinic Feb. 22 canton Balzar , Guayas Province, in the first half of 2013. People with hypertension are two to four times the risk of coronary heart disease (CHD ) , also reduced 5-6 mm Hg decrease in blood pressure of 20 -25 % CHD risk Among the targets we have, determine the type of nursing care that hypertensive patients 45 applies to age 75 who come to the clinic Feb. 22 Canton Balzar , in the first half of 2013. Also provide that type of food consumed diet patients 45 to 75 years old , Analyzing the type of exercise performed hypertensives . Its main hypothesis considers With the application of a guide to nursing care for hypertensive patients aged 45 to 75 years old, give a tool for caregivers to optimize care and improve the quality of life of patients ? . Coming to the conclusion that systemic hypertension affects approximately 20 % of the adult population of our community, is the leading cause of morbidity and motivates more consultations within the conditions of the circulatory system Ending the following recommendations as to motivate community residents to increase their interest to improve their health with respect to blood pressure, guidance to people in the community to be able to identify the risks that carries not perform a change in lifestyle . And Educate the public about dietary habits.